Two-electron-one-photon transitions in Cu9+-Zn collisions. (July 2015) - Guo, Yipan; Yang, Zhihu; Du, Shubin; Xu, Qiumei; Chang, Hongwei; Cai, Xiaohong
Synopsis: The two-electron-one-photon Kαα x-rays emissions from 80 MeV Cu 9+ -Zn collisions have been measured. These Kαα x-rays originate from the projectile ions and target atoms. It indicates that double K-vacancies appear in both Cu 9+ ions and Zn atoms.